Learning English Vocabulary in Nursing Context for Nursing Students - Puteri Novianty; Tenny Murtiningsih; Noor Aida Aflahah; Hafizhatu Nadia; Adi Jufriansah; Ajah Saputra (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
The background of this research is to find out how to learn and apply English vocabulary in the nursing class. This study aims to find out the right way to teach English vocabulary to nursing students at a private university in Banjarmasin. This type of research uses qualitative research methods with case studies. The research instrument used interviews. The research subjects were 4th semester nursing students at a private university in Banjarmasin. Nursing students learn English by taking turns reading, presenting in English. The problems encountered during learning activities in class are sometimes not understanding when the lecturer explains, because each lecturer has a different accent, and some say that they don't learn English from the basics, so it's rather difficult to understand. The way to solve the problems found is to listen to English songs more often and watch movies with English subtitles to find out new vocabs, and also don't forget to often speak English with friends. The application of vocabulary in nursing classes students apply their English to communicate with patients and communicate with fellow nurses, actually the application is richer to friends and plans to patients, but this patient has not been implemented yet, the plan is implemented in 7th semester.